Is it Phoeochroops Candèze, 1876 or Phaeochroops Candèze, 1876 (Coleoptera: Hybosoridae) when the Code provides no criteria for determining prevailing usage of a subsequent spelling? - Allsopp, Peter G.; Schoolmeesters, Paul (Zootaxa, 2026)
The status of Phoeochroops Candèze, 1876 and of five subsequent spellings is reviewed. Phoeochroops is confirmed as the correct original spelling by an act of the First Reviser, with Phoeocroops considered an incorrect subsequent spelling. Phaechroops, Paechroops and Phaeocroops are incorrect subsequent spellings and are not available names. Phaeochroops, although an incorrect subsequent spelling, is in prevailing usage and could be considered the valid name under Article 33.3.1 of the International Code of Zoological Nomenclature, except that the Code provides no criteria for determining what constitutes prevailing usage of a subsequent spelling, only of names. Modifications to the Code that would clearly define prevailing usage for alternative spellings are suggested.